2023
DOI: 10.1088/2051-672x/acc045
|View full text |Cite
|
Sign up to set email alerts
|

Correlating topographical characteristics of relaxed layer to tribology in Cu-Gr-TiC composite system

Abstract: The copper graphite composites are often being applied as bearing materials in various industries. In present investigation, the correlation between the topographical characteristics of relaxed layer to tribology in Cu-Gr-TiC composite system has been investigated. For this purpose, the flake powder metallurgy approach was used to fabricate Cu-Gr-TiC composites and the tribology of these composites was studied under lubricating (synthetic SAE20W40 motor oil) condition. Variable loads of 10 N-70 N, sliding velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, for the T4.5 composite (figure 3(b)) there is a rise in the Ti and C elemental dots suggesting an increase in content of TiC particles. The details from T4.5 composite mapping showed some agglomeration of particles at random places [19]. It is also observed that the clustering of graphite particles is reduced owing to hardening property of titanium carbide particles.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, for the T4.5 composite (figure 3(b)) there is a rise in the Ti and C elemental dots suggesting an increase in content of TiC particles. The details from T4.5 composite mapping showed some agglomeration of particles at random places [19]. It is also observed that the clustering of graphite particles is reduced owing to hardening property of titanium carbide particles.…”
Section: Resultsmentioning
confidence: 86%
“…Kumar and Devaraju [14] used response surface methodology to optimise hardness, ultimate tensile strength, density, porosity, and specific wear rate for the CRS/SiC reinforced aluminium composites. Singh et al [19] used RSM to examine how wear parameters affected wear and friction behaviour of B 4 C and SiC reinforced AA6082-T6 composites.…”
Section: Introductionmentioning
confidence: 99%
“…A material's hardness and strength can be increased by adding hard particles, primarily ceramic ones, to the matrix. Adding ceramic hard particles to composite materials allows makeup for a lack of strength and hardness [25]. To resolve this concern, a hybrid composite that combines solid lubricants like graphite with ceramic reinforcement can enhance the mechanical and wear properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al and Monkova et al investigated the effects of extreme braking conditions and different combination parameters on the performance of powder metallurgy friction materials, respectively [7,8]. Ankit et al studied the friction characteristics of Cu-Gr-TiC composites prepared by the flake powder metallurgical method [9]. Hussain et al studied the wear behavior of the aluminum hybrid composites developed through powder metallurgy [10].…”
Section: Introductionmentioning
confidence: 99%